Konflik Sosial Tokoh dalam Novel Home Sweet Loan Karya Almira Bastari - Ubaidillah, Muhammad Sya’bi; Novitasari, Lusy; Purnama, Ardian Pitra Satya (LEKSIS: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Literary works are one part of beautiful works of art that display beautiful values such as the novel “Home Sweet Loan” by Almira Bastari, are part of art that convey beautiful values both actually and imaginatively, providing entertainment and satisfaction to reader. This research aims to analyze the types of social conflict between characters, find out the factors that cause social conflict between characters, and find out the forms of resolution of social conflict between characters. The method used is descriptive qualitative, with a literature review approach that focuses on analyzing sentences or paragraphs related to social conflicts and their solutions. The research results revealed (1) types of social conflict between characters, including personal conflict, inter-social class conflict, and group conflict; (2) factors that trigger conflict, such as individual differences, social class and groups; (3) a form of conflict resolution, which consists of compromise and Stalemate. It is hoped that the results of this research will provide a deeper understanding of the social conflict in the novel, as well as being more useful in teaching literature.